User needs to the test: evaluating a Terminological Knowledge Base on the environment by trainee translators - Clara Inés López Rodríguez; Miriam Buendía Castro; Alejandro García Aragón (JoSTrans: The Journal of Specialised Translation)
Trainee translators and their use of lexicographical and terminographical resources when translating specialised texts can shed light on the close relation between Terminology, Lexicography, Translation and Knowledge Acquisition. Although the definition of users' profiles and their needs has been an habitual concern in Lexicography and Terminology research, there are not many studies dealing with methodological aspects in the design of empirical studies to evaluate lexicographic and terminographical resources. In this context, we designed a questionnaire to evaluate and validate for translation a terminological knowledge base on the environment, called EcoLexicon. The questionnaire was completed on-line by 3rd year students of the Faculty of Translation and Interpreting of the University of Granada (Spain). With this research, we aim at shedding some light on methodological aspects in the design of empirical studies to evaluate general and specialised resources for translating, as well as using the results obtained in the questionnaire to make some improvements to EcoLexicon for translators.